Hepatitis B Virus Exposure, Seroprotection Status, and Susceptibility in Health Care Workers From Lao People’s Democratic Republic: Cross-Sectional Study - Siriphone Virachith; Khanxayaphone Phakhounthong; Vilaysone Khounvisith; Mayfong Mayxay; Sengchanh Kounnavong; Somphou Sayasone; Judith M Hübschen; Antony P Black (JMIR Public Health and Surveillance, 2024)
Abstract BackgroundDespite the high prevalence of chronic hepatitis B virus (HBV) infection in adults in Lao People’s Democratic Republic (Lao PDR), Lao health care workers (HCWs) have previously been shown to have low levels of protection against infection. Furthermore, the prevalence of hepatitis D virus (HDV), which increases disease severity in individuals infected with HBV, is not known in Lao PDR. ObjectiveThis study aimed to estimate the exposure and seroprotection against HBV, as well as exposure to HDV, in Lao HCWs from 5 provinces. MethodsIn 2020, a total of 666 HCWs aged 20 to 65 years from 5 provinces of Lao PDR were recruited, and their sera were tested by enzyme-linked immunosorbent assay to determine their HBV and HDV coinfection status. ResultsHBV exposure, as indicated by the presence of anti–hepatitis B core antibodies, was 40.1% (267/666) overall and significantly higher for HCWs from Oudomxay province (21/31, 67.7%; adjusted odds ratio 3.69, 95% CI 1.68‐8.12; P= ConclusionsThe study found intermediate hepatitis B surface antigen prevalence among HCWs in Lao PDR, with no evidence of HDV coinfection. Notably, a significant proportion of HCWs remains susceptible to HBV, indicating a substantial gap in seroprotection against the disease.